Associations between Personal, Indoor, and Residential Outdoor Pollutant Concentrations: Implications for Exposure Assessment to Size-Fractionated Particulate Matter - Arhami, Mohammad; Polidori, Andrea; Delfino, Ralph J.; Tjoa, Thomas; Sioutas, Constantinos (Journal of the Air & Waste Management Association (1995), 2009)
The physical and chemical characteristics of indoor, outdoor, and personal quasi-ultrafine (<0.25 µm)-, accumulation (0.25-2.5 µm)-, and coarse (2.5-10 µm)-mode particles were studied at four different retirement communities in southern California between 2005 and 2007. Linear mixed-effects models and Spearman's correlation coefficients were then used to elucidate the relationships among size-segregated particulate matter (PM) levels, their particle components, and gaseous co-pollutants. Seasonal and spatial differences in the concentrations of all measured species were evaluated at all sites on the basis of P values for product terms. Outdoor quasi-ultrafine (UF) and, to a lesser extent, accumulation-mode particles were the two fractions that best correlated with outdoor concentrations of carbon monoxide (CO), nitrogen dioxide (NO 2 ), nitrogen oxides (NO x ; during both phases of the study), and ozone (O 3 ; only during the warmer months). Outdoor and indoor concentrations of CO, NO 2 , and NO x were more positively correlated to personal quasi-UF particles than larger size fractions. Despite these findings, it seems unlikely that these gaseous co-pollutants could confound epidemiologic associations between quasi-UF particles and adverse health effects. Overall, measured gaseous copollutants were weak surrogates of personal exposure to accumulation-mode PM, at least for subjects with similar exposure profiles and living in similar urban locations. Indoor sources were not significant contributors to personal exposure of accumulation and quasi-UF PM, which is predominantly influenced by primary emitted pollutants of outdoor origin. Correlations between personal coarse-mode PM and both outdoor and indoor gaseous co-pollutant concentrations were weak at all sites and during all seasons.